Metabolic bone disease among in-patients with rheumatoid arthritis. - Wordsworth, B; Vipond, S; Woods, C; Mowat, A (1984)
Twenty-five consecutive in-patients who had suffered from rheumatoid arthritis for at least five years were investigated radiologically, histologically and biochemically for evidence of metabolic bone disease. Dietary intake of vitamin D was universally well below recommended levels. Serum 25-hydroxycholecalciferol (25-OHD) concentrations did not correlate with dietary intake of vitamin D but correlated significantly with a sunlight exposure score (p less than 0.01). Despite seven patients having 25-OHD levels below the normal reference range, no cases of osteomalacia were found. Pathological fractures, often initially unrecognized, had occurred in the lower limb bones of seven patients in the previous five years. Those with fractures of the leg bones had evidence of more pronounced osteoporosis of the axial skeleton radiologically and histologically and five of the seven had been taking oral corticosteroids. There was close agreement between qualitative histological assessment of osteoporosis and radiographic evidence of vertebral collapse and those with the severest osteoporosis had lower serum levels of 25-OHD than the rest (p less than 0.02). Ten subjects had reduced xylose absorption tests, although frank malabsorption was not found, and in five patients studied the jejunal mucosa was normal.